Implementasi Sistem Informasi Point Of Sale Pada Pondok Makan Raja Sambel - Hermizahadiwidastra, Hermizahadiwidastra; Kartina, Riza; Wijaya, Khana (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2025)
This research aims to improve operational efficiency and accuracy of transaction data at Pondok Makan Raja Sambel through the implementation of a Point of Sale (POS) information system. This research method is a system development method that analyzes transaction data before and after system implementation. The point-of-sale system developed is web-based and integrated with the inventory management module. The research results show that the Implementation of the Point of Sale system has succeeded in increasing transaction speed, reducing recording errors, and providing more accurate information regarding sales and stock of goods. Apart from that, the Point of Sale system also makes it easier to prepare financial reports. An obstacle encountered during implementation was the resistance of some employees to the use of new technology. The implementation of the point of sale system has had a significant positive impact on the operational performance of Pondok Makan Raja Sambel.